Blood perfusion in left inferior and middle frontal gyrus predicts communication skills in schizophrenia. (30th April 2018) - Cantisani, Andrea; Stegmayer, Katharina; Federspiel, Andrea; Bohlhalter, Stephan; Wiest, Roland; Walther, Sebastian
Abstract: Schizophrenia is one of the most debilitating mental disorders, severely affecting patients' community functioning. Functional capacity (FC) describes the skills necessary for successful functional outcome (FO), such as financial knowledge or communication skills. We investigated whether resting-state cerebral blood flow (rCBF) measured at baseline with arterial spin labeling (ASL) would predict FC or FO at a 6-months follow-up in 27 schizophrenia patients. A negative linear association was noted between FC and rCBF in the left inferior and middle frontal gyrus, areas involved in language processing, suggesting a potential relationship between cerebral perfusion and prospective FC in schizophrenia. Highlights: Schizophrenia is characterized by poor functional capacity and functional outcome. A negative association between communication skills and blood perfusion was founnd. This association may be useful in the development of outcome and prognosis markers.